1984
DOI: 10.1002/jor.1100020414
|View full text |Cite
|
Sign up to set email alerts
|

In vivo strain patterns in the four major canine knee ligaments

Abstract: Using mercury gauges, we measured strains in vivo in the four major ligaments of the canine knee joint as the tibia was loaded in valgus or varus at fixed angles of knee flexion. Free axial rotation of the tibia on the femur was allowed. Forces up to 78.4 N were applied to the tibia, producing moments of approximately 9 N-m. We found that with valgus loading, significant strains were observed in the medial collateral ligament at extension. At 45 degrees of flexion, the medial collateral, posterior cruciate, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

1987
1987
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 29 publications
0
19
0
1
Order By: Relevance
“…First, the MCL is an extremely important structure in preventing medial joint opening and external tibial rotation in the human knee (Grood et al, 1981;Monahan et al, 1984;Palmer, 1938;Seering et al, 1980;Warren et al, 1974), and approximately 40% of all severe knee injuries involve the MCL (Miyasaka et al, 1991). Second, because of its planar geometry and size, the MCL is ideal for harvesting transverse samples for direct measurement of permeability.…”
Section: Tissue Harvestmentioning
confidence: 99%
“…First, the MCL is an extremely important structure in preventing medial joint opening and external tibial rotation in the human knee (Grood et al, 1981;Monahan et al, 1984;Palmer, 1938;Seering et al, 1980;Warren et al, 1974), and approximately 40% of all severe knee injuries involve the MCL (Miyasaka et al, 1991). Second, because of its planar geometry and size, the MCL is ideal for harvesting transverse samples for direct measurement of permeability.…”
Section: Tissue Harvestmentioning
confidence: 99%
“…The accuracy of this method also relies on homogeneous strain fields between the insertion sites. More recently, investigators have used liquid metal strain gages [85][86][87][88][89] or Hall effect strain transducers (HEST) [90][91][92][93] for localized measurement of ligament strain. These devices attach directly to the tissue substance and measure displacement between attachment points.…”
Section: Materials Testing Of Ligamentsmentioning
confidence: 99%
“…Sanjeevi et al 187,188 described the viscoelastic behavior of biological soft tissues with an equation similar to that of a Voigt-type spring and dashpot model. Dehoff 89 and Bingham and Dehoff 90 modified a continuum-based constitutive equation that had been used to characterize the nonlinear viscoelasticity of polymers to describe the behavior of soft biological tissues. Ligaments were modeled as an isotropic, viscoelastic material with fading memory.…”
Section: Viscoelastic Modelsmentioning
confidence: 99%
“…Sectioning studies have demonstrated that disruption of the sMCL allows for 5 mm of opening at 30°, and disruption of the entire MCL allows for 10 mm of opening at 30°. 19,30 Injuries to the MCL of the knee are common, particularly in contact sports such as American football. 1,5 Brophy et al 5 reported that MCL injuries were the most common injury found at the National Football League scouting combine.…”
mentioning
confidence: 99%